KAJIAN EVALUASI KINERJA INVESTASI KABUPATEN GARUT - Dadang Syafarudin; Jajang Sugiat (Eqien - Jurnal Ekonomi dan Bisnis, 2019)
Based on the National Spatial Planning and Spatial Planning of West Java Province in 2010, the role of Garut Regency is related to the spatial structure policy of the West Java region which sets two regional categories, namely the main area and the supporting area, in this case the Garut Regency as the central supporting region support economic growth in the main region together with the regions of Sukabumi and Cianjur Regencies. In the Provincial Spatial Planning plan that shows the dominant allocation of economic activity, Garut Regency is allocated for dry land agriculture activities, production forests, plantations, and fisheries. Investment Development Policy in Garut Regency is stipulated in the Regional Regulation of Garut Regency Number 14 of 2012 Regarding Investment Chapter III Direction of Investment Policy in the Region. The purpose of the Garut Regency Regional Investment Performance Evaluation Study is to provide convenience for the Regional Government in this case the Integrated Investment and Licensing Office and various other parties such as the general public, prospective investors in determining the choice of various alternative investment opportunities. the methodology to be carried out in the Garut Regency Investment Performance Evaluation Study, carried out several analyzes. These analyzes can be seen from the potential conditions (natural resources, human resources), supporting infrastructure, policies and economic conditions in the area around the Garut Regency Investment Area.